1993
DOI: 10.1128/jb.175.18.6002-6009.1993
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a region from the bacteriophage resistance plasmid pCI528 involved in its conjugative mobilization between Lactococcus strains

Abstract: A 10-kb HindIII fragment of pCI528 cloned into the nonconjugative shuttle vector pCI3340 could be transferred by conjugative mobilization from Lactococcus lactis subsp. lactis MG1363, whereas other HindIII fragments of pCI528 or the vector alone were nonmobilizable. Subcloning of this 10-kb region identified a 4.4-kb BglII-EcoRI fragment which contained all the DNA essential for transfer. Sequence analysis of a 2-kb region within this 4.4 kb-segment revealed a region rich in inverted repeats and two potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…However, no gene encoding conjugative function was present in pGdh442, indicating that pGdh442 is not self-transmissible but rather is mobilizable by the sex factor of MG1363 that encodes conjugative functions (Gasson et al, 1995), as reported elsewhere for many L. lactis plasmids (Lucey et al, 1993).…”
Section: Plasmid Mobilizationmentioning
confidence: 80%
“…However, no gene encoding conjugative function was present in pGdh442, indicating that pGdh442 is not self-transmissible but rather is mobilizable by the sex factor of MG1363 that encodes conjugative functions (Gasson et al, 1995), as reported elsewhere for many L. lactis plasmids (Lucey et al, 1993).…”
Section: Plasmid Mobilizationmentioning
confidence: 80%
“…Indeed, we have recently found that another conjugative plasmid, pCBG104 (10), encoding an undefined conjugative transfer system, is capable of mobilizing pRH001 (R. M. Hickey, D. P. Twomey, R. P. Ross, and C. Hill, unpublished work). However, in contrast to the oriT loci of pCI528 and pRS01, which can be mobilized by the ML3/712 class sex factor (33,38), the pMRC01 oriT is apparently not mobilized by this element. This inability to mobilize the pMRC01 oriT may be a reflection of inherent differences in the secondary structure of this element.…”
Section: ϫ4mentioning
confidence: 96%
“…1C). A similar sequence is also present in the self-transmissible conjugative lactococcal plasmids pRS01 (38) and pCI528 (33) and in several lactococcal plasmids, including pAH33 (41), pNZ4000 (48), pSRQ900 (16), pBL1 (34), and pWV01 (three copies present; 30). Plasmids from other lactic acid bacteria, such as the Lactobacillus plantarum phage resistance plasmid pLKS (15), the Lactobacillus helveticus cryptic plasmid pLH2 (43), and the Leuconostoc mesenteroides plasmid pTXL1 (accession no.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Self-transmissible conjugative plasmids have the ability to form effective cell-to-cell contact, while mobilization plasmids are only able to prepare their DNA for transfer (Steele and McKay 1989). In contrast, nonself-transferable plasmids contain only a cis-acting transfer origin (oriT) and mobA gene, while other conjugal functions have to be provided in trans from true conjugative plasmid or a chromosomally located sex factor (Lucey et al 1993;Lanka and Wilkins 1995). Conjugation has proven to be a useful gene transfer system for the genetic analysis of lactococci (Gasson 1990).…”
mentioning
confidence: 99%